REACTOGENICITY OF HETEROLOGOUS MRNA-BASED COVID-19 VACCINE BOOSTER IN YOUNG ADULTS IN INDONESIA- A SHORT COMMUNICATION.: COVID-19 vaccine booster reactogenicity in young adults - SURYADINATA, Neneng; CHRISTOPHER, Paulus Mario; IMANUELLY, Michelle; Wijaya, Ratna Sari; CUCUNAWANGSIH, Cucunawangsih; LUGITO, Nata Pratama Hardjo (African Journal of Infectious Diseases (AJID), 2023)
Background: Heterologous priming with the inactivated SARS-CoV-2 vaccine (CoronaVac) and boosting with mRNA-based COVID-19 vaccine (Moderna or Pfizer) is currently recommended in Indonesia. The reactogenicity data of these heterologous vaccine regimens are not entirely available, particularly in young adults.The present study, therefore, aimed to evaluate the solicited local and systemic reactions in the first seven days post-vaccination either with Moderna or Pfizer vaccine among previous recipients of two doses of CoronaVac. Materials and Methods: An electronic-based cross-sectional study was conducted among medical students at the Pelita Harapan University, Banten, Indonesia, who received mRNA-based COVID-19 vaccine following two doses of CoronaVac. Samples were collected using a cluster sampling technique. Comparison between groups was performed by Fisher’s exact test. Results: A total of 72 participants, with 23 (32%) of which received the Moderna vaccine and 49 (68%) received the Pfizer vaccine, were included in this study. The median age of participants was 21 (IQR 19-22) years old. The most common local and systemic events for mRNA-based COVID-19 vaccines were injection site pain, fever, headache, fatigue, myalgia, and arthralgia. Solicited local and systemic reactions were reported more frequently in Moderna recipients than Pfizer recipients. Most local and systemic reactions were graded as mild to moderate and did not lead to hospitalization. Conclusions: The reactogenicity of the heterologous prime-boost with CoronaVac and mRNA-based COVID-19 vaccine booster among young adults is reassuring, and no unexpected concerns were identified.